(untitled) (Costa Rican Journal of Guidance & Counseling, 2024)
Objective: Analyze the process of vocational development from the perspective of older adults in their life cycle stage, using the DOTS model proposed by Law and Watts. Methodology: This study was based on the naturalistic paradigm and used a case study design involving four older adults. Data were collected through interviews and four data collection techniques. For the analysis, a triangulation of the results collected was applied. Results: The perspective of older adults on their stage of the life cycle is influenced by multiple intrinsic and extrinsic vocational factors that have developed throughout their personal, emotional, work, and family experiences. Most participants agree that older adulthood can be a stage that allows them to continue learning new activities and fulfill dreams and goals that they had not achieved before. The DOTS model provides a path that encourages reflection and action in favor of each individual's personal needs as an active subject in society. Conclusions: This model considers and allows the analysis of what each participant can do for themselves according to their individual characteristics to take advantage of the opportunities offered by their environment. This reflects the importance of self-determination and empowerment of older adults in their vocational development and in the pursuit of fulfilling their goals and desires at this stage of life.